2012
DOI: 10.5858/arpa.2011-0511-oa
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis May Be a Disease of Recurrent, Tractional Injury to the Periphery of the Aging Lung: A Unifying Hypothesis Regarding Etiology and Pathogenesis

Abstract: Context.—Idiopathic pulmonary fibrosis is a progressive, fatal lung disease occurring in older individuals. Despite 50 years of accrued data about the disease, little progress has been made in slowing functional loss or in decreasing patient mortality. Objective.—To present a novel hypothesis on the etiology and pathogenesis of idiopathic pulmonary fibrosis. Design.—Published data are reviewed regarding the epidemiology, clinical presentation, natural history, radiologic findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 56 publications
0
88
1
2
Order By: Relevance
“…LESLIE [31] suggested that recurrent stretch injury caused by pressure changes during breathing may explain why fibrosis in IPF typically commences in the peripheral basal part of the lung. LESLIE [31] argues that in these areas the traction forces and alveolar collapse are greatest, leading to sheer stress, lung injury and activation of fibrotic cascades. By analogy, mechanical ventilation in IPF can be a risk factor for acute exacerbations of the pulmonary fibrosis [32].…”
Section: Pathophysiology Of Cough In Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…LESLIE [31] suggested that recurrent stretch injury caused by pressure changes during breathing may explain why fibrosis in IPF typically commences in the peripheral basal part of the lung. LESLIE [31] argues that in these areas the traction forces and alveolar collapse are greatest, leading to sheer stress, lung injury and activation of fibrotic cascades. By analogy, mechanical ventilation in IPF can be a risk factor for acute exacerbations of the pulmonary fibrosis [32].…”
Section: Pathophysiology Of Cough In Ipfmentioning
confidence: 99%
“…1: traction leading to a weaker lower oesophageal sphincter tonus [45]; 2: microaspiration inducing epithelial damage [38,46]; 3: restriction inducing instability of the upper airway [39]; 4: intermitted hypoxaemia promoting profibrotic mechanisms [49]; 5: increased cough reflex sensitivity [22][23][24][25][26][27][28][29][30][31]; 6: pressure causing stretch injury and activation of fibrotic mechanisms [31]; 7: microaspiration causing an inflammatory reaction blocking the airway [53]; 8: obstruction increasing trans-diaphragmatic pressure [51,52]; 9: aspiration directly and acid reflux indirectly stimulate the cough reflex [6,47]; 10: cough increasing trans-diaphragmatic pressure [47]; 11: less central inhibition and inflammation increasing cough reflex sensitivity [54]. sensory nerves.…”
Section: Figurementioning
confidence: 99%
“…Pathologic fibrogenesis is poorly understood with respect to its initiating events and mechanisms that maintain ongoing fibrosis. Evidence suggests that type II alveolar epithelial cells experience injuries that initiate mesenchymal cell migration, proliferation, and activation of profibrotic pathways (4,5). The resulting fibrosis is likely the summation of complex interactions between alveolar epithelial cells, resident fibroblasts, circulating fibrocytes, and infiltrating inflammatory cells.…”
mentioning
confidence: 99%
“…LESLIE et al [13] proposed that recurrent stretch injury, caused by pressure changes during breathing, promotes fibrosis. Cough might be an additional source of mechanical stress, and could theoretically contribute to a pro-fibrotic feedback loop.…”
mentioning
confidence: 99%